Primary Hyperparathyroidism in Pregnancy: Successful Parathyroidectomy during First Trimester - Niranjan Tachamo; Bidhya Timilsina; Rashmi Dhital; Theresa Lynn; Vasudev Magaji; Ilan Gabriely (Case Reports in Endocrinology)
Primary hyperparathyroidism in pregnancy can result in significant maternal and fetal complications. When indicated, prompt parathyroidectomy in the early second trimester is considered the treatment of choice. Pregnant patients with primary hyperparathyroidism who have an indication for parathyroidectomy during the first trimester represent a therapeutic challenge. We present the case of a 32-year-old primigravida who presented with symptomatic hypercalcemia from her primary hyperparathyroidism. She remained symptomatic despite aggressive conservative management and underwent parathyroidectomy in her first trimester with excellent outcomes.